Pedagogical use of ICT and oral communicative competence of the English language in students of the English language specialty, Faculty of Education, UNMSM 2019-II - Salcedo Godoy , Nancy (2024)
This study was carried out with the aim of analyzing how the pedagogical use of information and communication technologies (ICT) influences the oral communicative competence of English in students of the English specialty of the Faculty of Education of the UNMSM, during the period 2019-II. The research has a quantitative approach, it is classified as descriptive with a correlational-causal, cross-sectional and non-experimental design. The sample was composed of 15 students of said specialty. For data collection, the survey was used as a technique, employing a questionnaire to evaluate the use of ICT and a test to measure oral communication competence in English. To analyze the relationship between the variables, the Spearman coefficient was applied. As a main conclusion, it was found that there is a statistically significant influence between the pedagogical use of ICT and performance in oral communicative competence in English, with a high correlation of 0.828 and a p-value of 0.00. Likewise, a high correlation of 0.831 was identified between the use of ICT and oral expression, as well as a correlation of 0.816 with oral comprehension of English, both with a p-value of 0.00.